DESIGN AND MANUFACTURING A WOOD CHIPPER MACHINE - YAGOUBI, Naceur (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE Département de génie mécanique, 2023)
In my research, , where I touched on the definition of wood and what it is, and then we moved up to the definition of the history of the machine from its first use to the present day, and we also moved up to the speed and cutting power of the wood material, where I made a design for all aspects of the machine using SolidWorks . In the last chapter, which we can call the "design application chapter", where in this chapter I mentioned all the machines that contributed to the installation and manufacture of this machine, where I photographed all the machines of the nation involved in the manufacture and installation, as well as signing, welding and riveting machine parts, as well as the final and experimental demonstration of the machine. The process, i.e. the manufacturing process, was carried out according to three important stages, namely, study, design, and application, and finally the desired result was reached.
Option: MECHANICAL AND PRODUCTIVE MANUFACTURING